2010
DOI: 10.1007/s00125-010-1755-3
|View full text |Cite
|
Sign up to set email alerts
|

Is there an impatience genotype leading to non-adherence to long-term therapies?

Abstract: In chronic diseases such as diabetes, adherence to therapy aims to preserve health, which is a long-term objective, whereas non-adherence tends to present an immediate 'reward'. We propose that non-adherence, like addiction, is at least in part due to the fact that, for physiological, and maybe genetic reasons described in a new field, neuroeconomics, a number of people have a taste for the present rather than the future. Thus, for 'impatient patients' it is natural not to adhere to therapeutic prescriptions t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…Inversely, nonadherence is very frequent in teenagers27 and may simply represent one of the manifestations of disobedience that is a normal characteristic of this period of life, together with teenagers’ difficulty projecting themselves in the future 28. In an even more speculative mode, in the same way that the patience of individuals that leads to adherence24 may be, in part, genetically determined29 and only fully developed in adulthood30 (which may explain why adherence improves with age),13,3137 similar hypotheses may be proposed for obedience.…”
Section: Discussionmentioning
confidence: 99%
“…Inversely, nonadherence is very frequent in teenagers27 and may simply represent one of the manifestations of disobedience that is a normal characteristic of this period of life, together with teenagers’ difficulty projecting themselves in the future 28. In an even more speculative mode, in the same way that the patience of individuals that leads to adherence24 may be, in part, genetically determined29 and only fully developed in adulthood30 (which may explain why adherence improves with age),13,3137 similar hypotheses may be proposed for obedience.…”
Section: Discussionmentioning
confidence: 99%
“…The theory of neuroeconomics, an emerging field of study focusing on anomalies in the classical economics rationale, can provide important clues for understanding unreasonable human behavior regarding decisions over outcomes that occur at different time points 6,7. Neuroeconomic studies have demonstrated that humans and animals prefer rewards available to them in the short term over rewards only available in the long term.…”
Section: Introductionmentioning
confidence: 99%
“…The cause of nonadherence is complex and there are many factors that have been linked to increasing rates of nonadherence. These include factors related to the cost of the medications, socioeconomic status, and convenience . With increasing rates of poverty among those living in rural areas, overall lower median household income for rural dwellers compared to urban dwellers, reduced rates of insurance coverage for rural dwellers, and increased distance to health care services among individuals living in rural communities, one would assume the risk of nonadherence is increased among those living in rural communities …”
mentioning
confidence: 99%
“…These include factors related to the cost of the medications, socioeconomic status, and convenience. [10][11][12][13][14][15] With increasing rates of poverty…”
mentioning
confidence: 99%